IoT based Smart Farming System - Rathnamala, S.; Parameswari, C.; R.S, Sobana; Lakshmi.M, Veera (Journal of ISMAC, 2023)
The foundation of the economy and the most fundamental source of occupations is agriculture. Most people in the world depend on agriculture to sustain their daily existence. In India, crop production supports over 80% of the population. The majority of crop production needs to be handled by modern technologies because it can't be productive just through real-life activities. The initial approach is leveraging an novel water supply system with an innovative concept. This system is an expansion of the prior strategy that it highlights the characteristics that give a crop control over soil moisture, temperature, and a smart water system. These features also provide basic management in terms of precise continuous field information. A PC with Internet access keeps track of each of these activities to see whether they can be controlled.
Keywords: Temperature Sensor; Soil Moisture Sensor; PIR Sensor; GSM module